The relationship between social support, spiritual well-being, and depression in Christian clergy: a systematic literature review. Issue 10 (25th November 2020) - Edwards, Laura; Bretherton, Roger; Gresswell, Mark; Sabin-Farrell, Rachel
ABSTRACT: Rates of depression in Christian clergy have been reported as being more than three times that of the general population, and some studies have suggested this is associated with a lack of perceived social support or clergy-members' spiritual well-being. This systematic literature review aimed to identify studies of depression in clergy to assess evidence of the association between social support, spiritual well-being, and depression in this group. Effect sizes were standardised across studies and a narrative synthesis used to discuss findings. Higher rates of depression were found across all studies compared with global health estimates and particularly in those at risk of social isolation, specifically Catholic clergy. Small to moderate associations were found between clergy depression and both perceived social support and spiritual well-being. The quality of the studies identified was varied. Further research is required to explore clergy well-being, barriers to support seeking and clergy-members' spiritual well-being.